Neoliberal populism in Turkey and its crisis - Ümit Akcay (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
Turkey was shown as a model country by Western capitals in the early 2000s because it successfully embraced the neoliberal economic path and "moderate Islamist" values. In the last couple of years, however, Turkey has been in a state of turmoil, which has included the failure of the so-called democratization process and a rapid rise in authoritarianism. Surprisingly, the Justice and Development Party (AKP) of Turkey has been among a few political parties worldwide which have managed to stay in office, despite implementing a neoliberal economic model since 2002. This paper suggests that the "neoliberal populism" framework can be applied to understand the seemingly contradictory dynamics of the so-called success story of the AKP. First, the paper explains the main features of the neoliberal populist model in Turkey. This model is characterized by the implementation of neoliberal austerity measures alongside the introduction of a new welfare regime and the widening of financial inclusiveness. The main result of neoliberal populism is the enfeeblement of labor movement. Second, the paper argues that once the neoliberal populist model was established, it changed the structure of the political conflict. In this new structure, power struggles have taken the form of intra-elite conflict, rather than class struggle. The paper also suggests that a recent change to the executive presidential system in Turkey should be understood in the context of a continuing power struggle among the ruling classes, one that has been unfolding since 2007.
Keywords: P16; I38; J38; D74; H53; 330; Neoliberal populism; financial inclusion; social inclusion; Turkey